Viksit Bharat 2047 - Deepa Iranna Itagi (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India, as the world’s largest democracy and fifth largest economy, stands at the threshold of historic transformation. The Government of India’s Viksit Bharat 2047 vision outlines a roadmap for India’s evolution into a developed nation by its centenary of independence. Unlike earlier developmental strategies that emphasized only economic growth, this vision encompasses social inclusion, environmental sustainability, governance reforms, and global leadership. The study attempts to provide a comprehensive analysis of the multidimensional challenges and opportunities before India. It synthesizes existing literature on growth models, highlights the research gap, and proposes a conceptual framework for achieving the 2047 goals. The findings underscore the significance of human capital investment, digital innovation, institutional efficiency, and climate-conscious development as key drivers. Achieving this vision will require structural reforms, inclusive policies, and global cooperation.